Reactivity of Li14P6S22 as a Potential Solid Electrolyte for All‐Solid‐State Lithium‐Ion Batteries. (9th September 2018) - Doh, Chil‐Hoon; Ha, Yoon‐Cheol; Lee, You‐Jin; Yu, Ji‐Hyun
Abstract : The electrochemical reactivity of Li14 P6 S22 (Li7 P3 S11 ) as a sulfur‐based solid electrolyte for Li + conduction was evaluated by electrochemical cell tests and ab initio calculations to determine its utility for all‐solid‐state lithium secondary batteries. Reversible removal and incorporation of lithium into Li14 P6 S22 with a gradient of lithium concentration was confirmed as thermodynamically unfavorable. Otherwise, reductive/oxidative decomposition of Li14 P6 S22 by the addition/removal of lithium was thermodynamically favorable. The electrochemical stability window (ESW) of Li14 P6 S22 was 0.429 V between 1.860 and 2.289 V (Li/Li + ). The lowest potential of Li elimination was 2.289 V and occurred as oxidative decomposition. The highest potential of lithium addition was 1.860 V as reductive decomposition. Formation of Li14+ x P6 S22 and Li14− x P6 S22 could be simultaneously achieved with reductive and oxidative decomposition by applying negative and positive over‐potentials. The exposure of Li14 P6 S22 electrodes to positive and negative electric fields generated a large amount of irreversible specific capacity, which confirmed the oxidative and reductive decomposition. Considering the results of ab initio calculations on ESW and electrochemical cell tests, Li14 P6 S22 material should be protected from direct contact to the potential of cathode and anode so that it can appropriately serve as a solid electrolyte. The high Li + conductivity of Li14 P6 S22 might originate from temporal (kinetic) and endurable formation of Frenkel defects resulting in a Li‐deficient/excess composition of Li14 P6 S22 . Abstract :